Averting the rise of the dark side of social media: The role of sensitization and regulation - Baccarella, Christian; Wagner, Timm F.; Kietzmann, Jan H.; McCarthy, Ian P. (European Management Journal, 2020)
Social media have fundamentally influenced the way we live. Thus far, research has mainly focused on the ‘bright side’ of social media and the many advantages these platforms bring. More and more, however, research is also beginning to address the ‘dark side’ of social media. Dark side phenomena include cyberbullying, manipulation of elections, fear of missing out, social media addiction and the distribution of fake news. In this editorial for the management focus section of the European Management Journal, we propose two strategies (sensitizing and regulating) to manage this dark side of social media. Additionally, this editorial introduces the four articles included in this management focus section. We hope that the featured articles will help to encourage further research in this area.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Dark side; Regulation; Sensitizing; Social media; Technological progress